Modernizing Animal Disease Reporting in the State of Kansas - Davis, Mychal (My University, 2013)
The Kansas Department of Agriculture – Division of Animal Health (KDA-DAH) and the Kansas Department of Health and Environment (KDHE) are two state level health departments located in Topeka. KDA-DAH ensures public health and welfare of Kansas citizens through prevention, control, and eradication of infectious diseases. This is accomplished by regulating animal facilities through inspection and brand recognition. KDHE promotes health, protects the health, and prevents disease/injury among people in the state of Kansas. These goals are completed through surveillance and collaboration with healthcare officials to maintain vaccinations and records. This field experience was completed by collaborations between both agencies with the goal of improvement in reporting of diseases that are mandatory at the state and federal level. Projects that were completed during the field experience were for the improvement of: general knowledge regarding reportable diseases, improvement in surveillance, and standardization for disease reports. These improvements were implemented by the creation of the Disease Investigative Guideline, Joint Reportable Disease Guide, and a template for reporting diseases, specifically Brucella canis. The completed projects will advance through a trial run and will be assessed as necessary.
Keywords: Reportable diseases; Disease surveillance; Brucella canis; Public Health (0573)